2022
DOI: 10.3390/polym14050851
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Light Wavelength Conversion Materials and Their Applications in Functional Agricultural Films

Abstract: As new fluorescent materials, light wavelength conversion materials (light conversion agents) have attracted increasing attention from scientific researchers and agricultural materials companies due to their potential advantages in efficiently utilizing solar energy and increasing crop yield. According to the material properties, the light conversion agents can be divided into fluorescent dyes, organic rare-earth complexes, and inorganic rare-earth complexes. The current researches indicates that the fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Different light conversion agents added into the film may cause different light spectrum ( Kang et al, 2022 ). Additionally, the study found that rare-earth conversion film improved light transmittance, consistent with the previous research ( Liu et al, 2022 ). Rare-earth light conversion films can improve the greenhouse environment significantly.…”
Section: Discussionsupporting
confidence: 91%
“…Different light conversion agents added into the film may cause different light spectrum ( Kang et al, 2022 ). Additionally, the study found that rare-earth conversion film improved light transmittance, consistent with the previous research ( Liu et al, 2022 ). Rare-earth light conversion films can improve the greenhouse environment significantly.…”
Section: Discussionsupporting
confidence: 91%
“…Aggregation-induced emission (AIE) and TADF were utilized as two leading mechanisms in the design of organic light conversion agents. 123 Variety of π-conjugated organic scaffolds were already examined, with triphenylacrylonitrile proving to be a benchmark compound. For instance, Wang et al have optimized the parent triphenylacrylonitrile backbone by attaching additional aryls at positions 3 and 4 leading to derivatives 36a–e (Fig.…”
Section: Light Conversion Agentsmentioning
confidence: 99%
“…16,22 Even though much effort has been made to create red emission CLgens, such as copolymerization of itaconic anhydride and N-vinyl caprolactam, hydrolysis of poly PMV with NaOH, halogenated succinimide, and maleimide derivatives, and anionic polymerization of maleimide, 10,23−26 convert UV light and useless green light to blue (400−500 nm) or red light (600−700 nm) and boost the production of the crop as a result of the selective absorption ability of chlorophyll A, chlorophyll B, and other photosynthetic organisms in plants. 27,28 However, traditional light conversions agents, such as fluorescent dyes or rare-earth complexes, is suffered enough from poor photostability, high cost, bad compatibility, and difficult degradation processes. A new type of light conversion agent is urgently needed.…”
Section: Introductionmentioning
confidence: 99%